Superposition of chemical shifts in NMR spectra can be overcome to determine automatically the structure of a protein. Issue 2 (2003) - Auguin Auguin, D. D.; Catherinot Catherinot, V. V.; Malliavin Malliavin, T. E. T. E.; Pons Pons, J. L. J. L.; Delsuc Delsuc, M. A. M. A.
Abstract : We are here addressing the problem of the automatic determination of a protein structure at atomic resolution, by using only the signal recorded on three spectra: 2D 15 N HSQC, 3D 15 N NOESY-HSQC and TOCSY-HSQC. A modified version of the neural network RESCUE (J.L. Pons and M.A. Delsuc, J. Biomol. NMR 15 (1999), 15−26), N15-RESCUE, is developed in order to predict the amino-acid type from only the 15 N, HN, H α and H β chemical shifts. The spatial distances between protein residues are estimated by automatic comparison of columns extracted from a 3D 15 N NOESY-HSQC spectrum, using the FIRE method (T.E. Malliavin, P. Barthe and M.A. Delsuc, Theor. Chem. Accts 106 (2001), 91−97). The predictions provided by both FIRE and N15-RESCUE methods are then used for the determination of a preliminary NMR structure of the protein p8. A mean RMSD value of 2.31±0.86 Å is observed between the coordinates of heavy atoms from helices α I and α II, and the α III helix is taking random orientations with respect to the other helices. This random orientation is a consequence of the lack of predicted proximities between α III and α II, and is in agreement with other independent observations made on p8 structure.